The Influence of FOMO (Fear of Missing Out) on Generation Z's Purchasing Decisions in the Context of TikTok (A Case Study of Students of the 2021-2022 Class of Nahdlatul Ulama University, Cirebon) - tono, Tono Wartono; Darmun, Darmun; Nurauliah, Nurlani (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aims to determine the influence of the Fear of Missing Out (FOMO) phenomenon on purchasing decisions among Generation Z, particularly among students of the 2021-2022 batch at Nahdlatul Ulama University Cirebon in the context of using the TikTok application. The population of Generation Z students in this study was 246 students, while the sample taken based on the Slovin formula was 71 students. The method used in this study is a causal research method with simple linear regression analysis using a quantitative approach and data collection techniques through questionnaires. The research instrument was tested for validity and reliability before use. The results of the regression analysis show that the t- count value of 15.259 is greater than the t-table value of 1.667, and the significance value of 0.001 is less than 0.05. This indicates that FOMO has a positive and significant influence on purchasing decisions among Generation Z. Thus, the alternative hypothesis (Ha) in this study is accepted, while the null hypothesis (Ho) is rejected. In conclusion, FOMO has a strong influence in driving Generation Z, particularly students, to make purchasing decisions for items they see or encounter through TikTok.